Implementasi Akad Mudharabah dalam Produk TABAH (Tabungan Mudharabah) di KSPPS BMT NU Cabang Genteng - Nur Alwi Muhammad; Muhammad Kanzul Fikri (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
The development of the Islamic financial sector in Indonesia has shown significant growth, in line with increasing public awareness of the importance of a sharia-based economic system. One of the microfinance institutions that plays a role in supporting this system is Baitul Maal wat Tamwil (BMT). This study aims to analyze the implementation of the mudharabah contract in the TABAH (Mudharabah Savings) product at the KSPPS BMT NU Genteng Branch. This research method uses a descriptive qualitative approach with data collection techniques through literature studies. The results show that the TABAH product at the KSPPS BMT NU Genteng Branch uses a mudharabah mutlaqah contract, where the customer acts as the shahibul maal and the BMT as the mudharib. The profit sharing ratio applied is 40% for the customer, with a calculation mechanism based on the average daily balance. The application of the mudharabah contract in this product has fulfilled the pillars and principles of sharia by reflecting aspects of transparency, fairness, and accountability in fund management. This study provides academic contributions to the development of Islamic financial theory as well as practical benefits for optimizing fund management in Islamic microfinance institutions.